Vaccine Prevention of Pneumococcal Infection in Children - Alexander A. Baranov; Leyla S. Namazova-Baranova; Nikolay I. Brico; Yurii V. Lobzin; Roman S. Коzlov; Mikhail P. Kostinov; Irina S. Koroleva; Alla V. Rudakova; Sergey V. Sidorenko; Vladimir K. Tatochenko; Susanna M. Kharit; Marina V. Fedoseenko; et al. (Педиатрическая фармакология)
Pneumococcal infection remains one of the leading reasons for infant mortality from vaccine-preventable infections. Today vaccination is the most effective way to prevent diseases caused by antibiotic-resistant pneumococci. In the article, authors present current approaches to vaccinal prevention of pneumococcal diseases. The plan of action for carrying out active immunoprophylaxis of pneumococcal infection is explained in detail for both healthy children and patients from risk groups for severe pneumococcal diseases development. The published work is based on key points of the guidelines of the Ministry of Health of the Russian Federation on vaccinal prevention of pneumococcal infection (developed and approved by the professional association of pediatricians «The Union of Pediatricians of Russia»).